Increased prevalence of eating disorders as a biopsychosocial implication of food allergy. - Barbara Wróblewska; Anna Maria Szyc; Lidia Hanna Markiewicz; Magdalena Zakrzewska; Ewa Romaszko (PLoS ONE)
Introduction The study evaluates the impact of biopsychosocial factors involved in food allergy (FA) on the prevalence of eating disorders (ED). For the 5-year follow-up studies, 75 participants (aged 1-14 years) with early-onset FA and 81 healthy peers were included. Method Participants were diagnosed with FA using antibody/cytokine content immunoassay tests. Medical history, including BMI z-scores, was completed using data obtained in response to a validated allergic questionnaire that incorporated the SCOFF and EAT-8 screening questionnaires for ED. FA was confirmed if total IgE was elevated, specific sIgE to food allergens exceeded 0.7 kUA/L and if manifestations were observed. Screening for ED was considered positive if two or more SCOFF and EAT-8 items were confirmed. Results In the FA+ group, 50% of female participants and 6.7% of their healthy female peers reported ED. An ED+ result was more frequent in FA+ individuals than in their healthy peers (p = 0.046) although the association is weak. In the FA+/ED+ group, 25.3% of the participants were underweight, and 14.7% were overweight compared to their peers where this reached respectively 4.2% and 2.8% (p<0.005). 74% of the FA+/ED+ individuals reported elimination diet implementation and only 15% declared it was medically consulted. The prevalence of ED in the FA+ male group was consistently correlated with lack of confidence in FA issues (r = 0.5424) and in the FA+ female group with applied medical procedures (r = 0.7069; p<0.005). Conclusion These findings suggest that participants with FA especially struggling with lack of confidence in FA issues and those following an uncontrolled, restrictive elimination diet are more prone to food aversion and ED than their healthy peers. Applied procedures are necessary, and their neglect is associated with FA deterioration; however, the possibility of ED and biopsychosocial implications development should not be underestimated.